Tobacco dependence and motivation to quit smoking: an identity-based framework (Adicción al tabaco y motivación para dejar de fumar: una perspectiva identitaria). Issue 2 (4th May 2021) - Blondé, Jérôme; Falomir-Pichastor, Juan-Manuel
ABSTRACT: Literature has extensively shown that tobacco dependence is negatively associated with motivation to quit smoking. In this research, we aimed to account for this negative relationship by adopting an identity-based framework. More specifically, we hypothesized that tobacco dependence constitutes an identity threat that smokers seek to manage by diminishing their motivation to quit. To assess whether such a mechanism is at work, we used a self-affirmation manipulation across two independent studies that were pooled into one ( N = 308). More specifically, we asked daily smokers to report their tobacco dependence prior to manipulating self-affirmation. Then, we assessed their motivation to quit. Results demonstrated that, among high-dependent smokers, those who were self-affirmed reported higher motivation to quit than those who were not. Self-affirmation had no effect among low-dependent smokers. These findings illuminate the idea that an interpretation in terms of identity processes can offer new insights into understanding tobacco dependence and its consequences on smokers' motivation to quit.